Difai Fırkası'nın teşkilatlanması ve faaliyetleri (1906-1908) - Böke, Ozan (My University, 2020)
1801 yılından itibaren Güney Kafkasya’da hızla ilerleyen Çarlık Rusyası, 1828-1829 yıllarında bölgede hâkimiyeti tamamen ele aldı. Buradaki varlığını sağlamlaştırmak isteyen Çarlık idaresi Güney Azerbaycan ve Osmanlı sınırlarında yaşayan Ermenileri bölgeye taşıyarak buradaki Ermeni nüfusunu arttırdı. 1800’lü yılların sonlarında Ermenilerin artan çetecilik faaliyetleri Osmanlı topraklarında başarıya ulaşamayınca yönünü Güney Kafkasya’ya çevirdi. 1904 yılından itibaren Taşnaksutyun, programına Güney Kafkasya’yı ekledi. 1905 Rus Devrimi ile birlikte oluşan kaotik ortamdan Taşnaksutyun faydalanmak isteyerek Güney Kafkasya’da Azerbaycan Türklerine yönelik saldırılarda bulundu. Yaklaşık iki yıl süren Türk-Ermeni çatışmalarının sonucunda Türkler kendi haklarını savunacak bir teşkilat kurmaya kararına vardılar. 1906 yılının Ağustos ayında Difai Fırkası Gence’de kuruldu. Fırka yaklaşık iki yıl kadar kısa süren ömründe Rus idarecilere karşı suikastlar düzenledi. Bununla birlikte Türk, Ermeni ve Gürcülerin Güney Kafkasya’da barış içerisinde yaşamaları gerektiğini savundu. Müslümanların sosyal hayatlarını düzenleyecek ve onları eğitecek faaliyetler de gerçekleştirdi. 1908 yılının sonlarında Difai, Rus idaresinin artan baskıları sonucu faaliyetlerine son verdi.

Proceeding rapidly in the South Caucasus since 1801 Tsarist Russia, completely took over the domination in the region between 1828 and 1829. The Tsarist administration, which wanted to consolidate its presence here, increased the Armenian population here by moving Armenians living in the borders of South Azerbaijan and the Ottoman Empire to the region. When the increasing ganging activities of the Armenians did not succeed in the Ottoman lands in the late 1800s, it turned its direction to the South Caucasus. Since 1904, it added the South Caucasus to the Dashnaktsutyun program. Dashnaktsutyun wanted to take advantage of the chaotic environment that occurred with the 1905 Russian Revolution and attacked the Azerbaijan Turks in the South Caucasus. At the end of the Turkish-Armenian conflicts that lasted for about two years, the Turks decided to establish an organization that would defend their rights.In August 1906, the Difai Party was established in Ganja. The organization carried out assassinations against Russian administrators in a life span of about two years. Nevertheless, it argued that Turks, Armenians, and Georgians should live in peace in the South Caucasus. It also carried out activities to organize and educate Muslims' social lives. In late 1908, Difai ended its activities as a result of the increasing pressure from the Russian administration.
Keywords: Azerbaijan Turks; Azerbaycan Türkleri; Dashnaktsutyun; Difai Fırkası; Güney Kafkasya; History; South Caucasus; Tarih; Taşnaksutyun; Turkey; Turkish-Armenian conflicts; Türk-Ermeni Çatışmaları Difai Party; Türkiye